La crisis agraria de 1878-1881 en León - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1988)
In this paper, the influence of the agrarian crisis between 1879 and 1881 on the economy and society in León (Spain) is described. Whith the data provided by the newspapers about de prices of cereals, the lack of fluidity in the marketing of basic products during the crisis as well as the social response to it: the debate around the social issue, the socialism, and the charitable and educative enterprises emerging in those years is analyzed.